Working Paper 35: Social network analysis applied to illegal wildlife trade between East Africa and Southeast Asia (Basel Institute on Governance Working Papers, 2021)
This report presents the findings of a novel application of social network analysis (SNA) to study a criminal network surrounding an East Africa-based wildlife trafficker. This technique focuses on understanding structural, functional and sociometric characteristics of networks by mapping social interactions between individuals and groups. Particularly, the research studies how wildlife trafficking happens, and, in doing so, offers several promising avenues to curb it. SNA makes it possible to deconstruct the criminal network in question and identity its key individuals, operative functions and flows of goods, information and money. In turn, this can sustain the activities of investigators and prosecutors to discover new leads and suspects, or to better understand the meaning of financial and information flows.    The research has been conducted under a project of PMI Impact aimed at stopping corruption from fuelling illegal wildlife trade (IWT) between East Africa and Southeast Asia.  The results show that by combining SNA (a primarily quantitative method) with network ethnography (a qualitative method), we can gain important new insights into the structures, functions and mechanisms of crime networks engaged in IWT. This paper is part of the Basel Institute on Governance Working Paper Series, ISSN: 2624-9650.This report was funded by PMI IMPACT, a grant award initiative of Philip Morris International (PMI). In the performance of their research, the authors maintained full independence from PMI. The views and opinions expressed in this document are those of the authors and do not necessarily reflect the views of PMI. Neither PMI, nor any of its affiliates, nor any person acting on their behalf may be held responsible for any use which may be made of the information contained herein.